2015
DOI: 10.1186/s12889-015-2491-x
|View full text |Cite
|
Sign up to set email alerts
|

Work environments and HIV prevention: a qualitative review and meta-synthesis of sex worker narratives

Abstract: BackgroundSex workers (SWs) experience a disproportionately high burden of HIV, with evidence indicating that complex and dynamic factors within work environments play a critical role in mitigating or producing HIV risks in sex work. In light of sweeping policy efforts to further criminalize sex work globally, coupled with emerging calls for structural responses situated in labour and human-rights frameworks, this meta-synthesis of the qualitative and ethnographic literature sought to examine SWs’ narratives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 60 publications
(146 reference statements)
3
60
0
Order By: Relevance
“…Specifically, institutional barriers that may affect obtainment of health services for im/migrant SWs include fear of disclosing sex work to health providers, foregoing care in order to continue earning income, denial or delay of public health insurance, high cost of private health insurance, and ineligibility for social assistance and subsidized housing (Anderson et al, 2015; Goldenberg, Duff, & Krusi, 2015; Oxman-Martinez et al, 2005). Not having a provincial health insurance card was strongly correlated with reporting institutional-level barriers to health care among SWs, as determined by a researcher in Vancouver (Socías et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, institutional barriers that may affect obtainment of health services for im/migrant SWs include fear of disclosing sex work to health providers, foregoing care in order to continue earning income, denial or delay of public health insurance, high cost of private health insurance, and ineligibility for social assistance and subsidized housing (Anderson et al, 2015; Goldenberg, Duff, & Krusi, 2015; Oxman-Martinez et al, 2005). Not having a provincial health insurance card was strongly correlated with reporting institutional-level barriers to health care among SWs, as determined by a researcher in Vancouver (Socías et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The fluidity of this finding, where only a sub-set of low paid FSWs were most at risk for inconsistent condom use, stands in contrast to traditional frameworks of sex work environments, where economic status and type of solicitation strategy inform relatively fixed socio-environmental influences on FSW condom practices [17,1922]. Our findings underscore a need to devise more compatible frameworks to assess risks within sex work environments, which account for the varied effects of mobile phones on FSW condom practices.…”
Section: Discussionmentioning
confidence: 99%
“…Research to date has demonstrated that the economic status of a FSW (e.g., low or high paid FSW) is closely linked to how effectively a FSW safely navigates within sex work environments and in turn, the level of formal or informal support to enable safe sexual practices with clients [1723]. This is consistent with findings that economic debt and more generally, economic vulnerability, contributes to HIV risk for sex workers [1,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The objectives of this study are to estimate the prevalence of physical and sexual violence among FSW in Abidjan, Côte d’Ivoire and identify associated structural determinants in the work environment, HIV related outcomes, and experience in accessing health services.…”
Section: Introductionmentioning
confidence: 99%